2013
DOI: 10.1177/1534650113510398
|View full text |Cite
|
Sign up to set email alerts
|

Involving Parents in Cognitive-Behavioral Therapy for Child Anxiety Problems

Abstract: This case study examines how parents can be incorporated into all aspects of cognitive-behavioral therapy (CBT) for child anxiety problems. This is an important issue, because although there are strong theoretical and empirical reasons for incorporating parents into treatment, evidence from randomized controlled trials has so far been inconclusive about whether outcomes are improved by involving parents. This case study describes the clinical benefits of a balanced focus on parent and child factors for "Laura,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Compared with traditional, child-focused, cognitive–behavioral interventions, the Building Confidence intervention shows benefits above and beyond those of traditional therapy (Wood, Piacentini, Southam-Gerow, Chu, & Sigman, 2006). Such findings build on the results of other case studies that describe successful outcomes when involving caregivers in the treatment of childhood anxiety problems (e.g., Anderson, 2004; Krain, Hudson, Coles, & Kendall, 2002; Michael, Payne, & Albright, 2012; Siddaway, Wood, & Cartwright-Hatton, 2014); however, descriptions of the Building Confidence intervention and its outcomes are rarer in the literature.…”
Section: Theoretical and Research Basis For Treatmentsupporting
confidence: 70%
“…Compared with traditional, child-focused, cognitive–behavioral interventions, the Building Confidence intervention shows benefits above and beyond those of traditional therapy (Wood, Piacentini, Southam-Gerow, Chu, & Sigman, 2006). Such findings build on the results of other case studies that describe successful outcomes when involving caregivers in the treatment of childhood anxiety problems (e.g., Anderson, 2004; Krain, Hudson, Coles, & Kendall, 2002; Michael, Payne, & Albright, 2012; Siddaway, Wood, & Cartwright-Hatton, 2014); however, descriptions of the Building Confidence intervention and its outcomes are rarer in the literature.…”
Section: Theoretical and Research Basis For Treatmentsupporting
confidence: 70%
“…Our results do however corroborate previous work with face to face CBT in children which suggests treatment outcomes can be improved with parental involvement (Barrett et al 1996 ; Creswell and Cartwright-Hatton 2007). It has been suggested that parental involvement may aid the successful learning and application of new skills, perspectives and applying specific strategies learned in therapy into real life (Siddaway et al 2014 ; Spence et al 2000 ; Stallard 2005 ; Thirlwall et al 2013 ). As such their children might be more likely to continue to understand and implement therapeutic strategies and so make therapeutic gains (Thirlwall et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such their children might be more likely to continue to understand and implement therapeutic strategies and so make therapeutic gains (Thirlwall et al 2013 ). Parental involvement may also aid changes in family processes and parental risk factors implicated in the development and maintenance of childhood anxiety (Barrett et al 1996 ; Siddaway et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that past treatment did produce meaningful change because it placed a primary focus on her anxiety but not the underlying environmental factors contributing and how they interacted with each other to impair Evie’s functioning. Indeed, Evie’s past treatment did not include parent consultation, which has been found to improve a child’s outcome in psychotherapy (Fricker-Elhai, Ruggiero, & Smith, 2005; LeBlanc & Ritchie, 2001; Siddaway, Wood, & Cartwright-Hatton, 2014) and entailed only behavioral coping skills for anxiety, per Evie’s mother’s report.…”
Section: Course Of Treatment and Assessment Of Progressmentioning
confidence: 99%